Framing governance a content analysis of selected blog entries of Davao City councilor Peter T. Laviña - Laviña, Allen Mae S.
This study was undertaken to identify how Davao City Councilor Peter Laviña frames governance issues in his blogs through a content analysis of selected twenty three blog posts of Councilor Laviña on governance matters. The researchers looked for framing devices, such as keywords, sources of information, reinforcing clusters of facts or judgments, visual images, metaphors, concluding statements., etc., present in each of the sample posts and identified how Councilor Laviña applied these devices. Councilor Laviña writes his blogs in a conversational manner, which makes his blogs a non-intimidating venue of communication between him as a public official and readers as citizens. Among the framing devices that were looked for in the blog samples, the most commonly used are: sources of information and reinforcing clusters of facts or judgments. These framing devices are regularly presented with or through hyperlinks. The use of hyperlinks make the blogs ( as a medium for conveying information) of Councilor Laviña more accurate and reliable, since the hyperlinks usually lead to web pages or online sites of the mainstream print media or government agencies. The least used device by Laviña is the metaphor framing device. Most of the blog samples are written in a negative and simple treatment, and in an interpretative tone. This research may serve as a baseline data for studies on how framing can be done in new media. In addition, this study may help councilor Laviña in promoting blogging as a tool to promote participatory governance.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts